Precommitment, Transparency and Monetary Policy - Petra Maria Geraats (Deutsche Bundesbank, 2001)
Conventional wisdom says that commitment eliminates the inflationary bias of monetary policy. However, this paper shows that the inflation bias can persist even when the central bank commits. A simple model is presented in which the central bank precommits by setting the policy instrument, and the subsequent adjustment of inflation expectations is part of the transmission mechanism. Generally there is still an inflation bias, despite the absence of a time-inconsistency problem. It is caused by uncertainty about the economic disturbances to which the central bank responds. Only perfect transparency about economic information completely eliminates the inflation bias. – – Üblicherweise wird angenommen, dass ein Inflationsbias verschwindet, wenn sich eine Zentralbank glaubwürdig im voraus auf ihre Politik festlegt. Dieses Papier zeigt, dass ein Inflationsbias trotzdem fortbestehen kann. Es wird ein einfaches Modell dargestellt, in dem die Zentralbank im voraus ihre Instrumente festlegt und die anschließende Anpassung der Inflationserwartungen Teil des Transmissionsprozesses ist. Im allgemeinen existiert ein Inflationsbias weiter, obwohl kein Zeitinkonsistenzproblem mehr auftritt. Ursache ist die Unsicherheit über die ökonomischen Störungen, auf die die Zentralbank reagiert. Nur vollkommene Transparenz hinsichtlich der Informationen beseitigt vollständig den Inflationsbias.
Keywords: E52; E42; E58; 330; Geldpolitik; Geldpolitisches Ziel; Regelgebundene Politik; Glaubwürdigkeit; Inflation; Inflationserwartung; Risiko; Staatliche Information; Vollkommene Information; commitment; inflation bias